2014
DOI: 10.1049/iet-bmt.2012.0043
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded multimodal biometric recognition framework

Abstract: A practically viable multi-biometric recognition system should not only be stable, robust and accurate but should also adhere to real-time processing speed and memory constraints. This study proposes a cascaded classifier-based framework for use in biometric recognition systems. The proposed framework utilises a set of weak classifiers to reduce the enrolled users' dataset to a small list of candidate users. This list is then used by a strong classifier set as the final stage of the cascade to formulate the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Multimodal identification procedure is developed by integrating data from several biometric sources. Baig et al [19] suggested a cascaded classifier-based model for utilization in biometrics recognition. The suggested model uses a set of weak classifiers for decreasing registered users' database to a smaller set of candidate users.…”
Section: Related Workmentioning
confidence: 99%
“…Multimodal identification procedure is developed by integrating data from several biometric sources. Baig et al [19] suggested a cascaded classifier-based model for utilization in biometrics recognition. The suggested model uses a set of weak classifiers for decreasing registered users' database to a smaller set of candidate users.…”
Section: Related Workmentioning
confidence: 99%
“…ii. As a result, interdisciplinary researchers, scientists and various research committees try to mitigate the effect of covariates challenges of the face image of animals using computer vision approaches [74][75][76]. The effects of covariates are significant problems for representation, detection and classification of species or individuals.…”
Section: Fundamental Requirements For Promising Applicationsmentioning
confidence: 99%